ANALISIS STRATEGI PEMASARAN PRODUK ARRUM HAJI DALAM MENINGKATKAN JUMLAH NASABAH PADA PT. PEGADAIAN SYARIAH UNIT MANGGIS - Hovi Vatul Rahma; Zuwardi (CV. Adiba Aisha Amira, 2023)
This study aims to find out how the marketing strategy for arrum haji products is in facing competition between other Islamic financial institutions. In this thesis, the research used is field research (field research) which is descriptive qualitative by using SWOT analysis. Therefore, the author must know how the state of the company, namely internal factors and external factors that influence the existing marketing strategy of the company. The results of this study indicate that to market arrum haji products at PT. Pegadaian Syariah Manggis Unit Bukittinggi by maintaining strength and making the most of available opportunities to achieve product marketing strategies by improving marketing strategies can be carried out through promotions with social media with technological advances and by making brochures or banners about Arrum Haji products of the Manggis Syariah Pawnshop unit. Based on the analysis on the combination of the SWOT matrix strategy for marketing arrum haji products, the SO strategy was obtained with a total score of 3.84, namely introducing that arrum haji products at sharia pawnshops are in accordance with Islamic sharia, increasing publications about arrum haji products through social media and print media, and activate promos regarding arrum haji products at every event in the community. As for the implementation of arrum haji products at sharia pawnshops, the principle of caution is used so that in every activity we are always careful so that we can protect the data and funds entrusted. Applying the principles of justice, the principle of trust and the principle of togetherness.